Shaking-table tests on reinforced concrete frames with different isolation systems. - Dolce, Mauro (Earthquake engineering & structural dynamics.)
The effectiveness of seismic isolation in protecting structural and non-structural elements from damage has been assessed in an extensive programme of shaking-table tests, carried out on four identical 1/3.3-scale, two-dimensional, reinforced concrete (R/C) frames. Four different isolation systems were considered, namely: (i) rubber-based, (ii) steel-based, (iii) shape memory alloy (SMA)-based and (iv) hybrid, i.e. based on both SMA and steel components, isolation systems. This paper presents a comprehensive overview of the main results of the experimental tests on base-isolated models, whose structural response is described through: (i) maximum base displacements; (ii) maximum interstorey drifts; (iii) maximum storey accelerations and (iv) maximum storey shear forces. The evolution of the fundamental frequency of vibration of the R/C frame during the tests is also described. The beneficial effects of using base isolation resulted in no or slight damage, under strong earthquakes, to both structural and non-structural members, as well as to the internal content of the building. The comparison with the experimental results obtained in shaking-table tests on similar fixed-base models emphasizes these positive aspects. Finally, advantages and drawbacks related to the use of each isolation system are discussed in the paper.